Role of 18F-FDG PET-CT in Urethral Malignant Melanoma and Analysis of the UK Guidelines on Ano-uro-genital Melanomas - Mahato, Abhishek; Jain, Anurag; Manoj, M.G.; Joshi, Richa (World Journal of Nuclear Medicine, 2023)
Urethral melanomas are a rare subtype of noncutaneous melanomas. The disease has a tendency to have skip lesions and early metastases as compared with cutaneous melanomas. The role of fluorine-18 fluorodeoxyglucose (18F-FDG) positron emission tomography computed tomography (PET-CT) is well established in cases of cutaneous melanomas and is recommended by the National Comprehensive Cancer Network (NCCN) for stage IIB to IV cancer. There are no established guidelines on the management of noncutaneous melanomas; however, a recently published United Kingdom national guideline aims to streamline the management of ano-uro-genital melanomas. The guideline describes a very limited role in the use of 18F-FDG PET-CT in this case scenario. The tendency to skip lesions, early metastases, involvement of brain parenchyma, and finally the usage of anti-PD-1 medications are key areas where 18F-FDG PET-CT has shown superiority over CT scan. With this case report, we aim to highlight the strength of 18F-FDG PET-CT in the management of urethral melanomas, which can be extrapolated to other ano-uro-genital melanomas.
Keywords: ano-uro-genital melanoma; FDG PET-CT; mucosal melanoma; UK guidelines; urethral melanoma